Sustaining the higher education hub model: the challenge of adequate academic and social support structures for international students / Cameron Richards and Mohd Ismail Abd Aziz. - Richards, Cameron; Abd Aziz, Mohd Ismail (Universiti Teknologi MARA Cawangan Selangor, 2011)
In recent years, the Education Hub (EH) concept has perhaps become the single most important focus of higher education policy in most Asian countries. A particular Asian Education Hub model (e.g. Cheng, 2010) is now globally influential with its emphasis on how governments can harness direct as well as indirect economic benefits of a higher education system. Such a model aims to prepare students for employment in an emerging global economy and also to attract fee-paying international students in terms of education as not just a public good but a key and increasingly important area of national investment and economic development. In a related paper which focused on a comparison between distinct Malaysian and Singaporean versions of Asian EH l models developed over the last two decades (Richards, 2011c), we investigated the dangers as well as opportunities at stake. In this paper, we investigate the linked idea that sufficient academic and social support structures for supporting international as well as local students provide the crucial key to the factors of sustainability needed to support the various versions of the general strategy of Higher Education internationalisation.